Musculoskeletal Pain: A New Algorithm for Differential Diagnosis of a Cardinal Symptom in Pediatrics - Tallen, G.; Bielack, S.; Henze, G.; Horneff, G.; Korinthenberg, R.; Lawrenz, B.; Niehues, T.; Peitz, J.; Placzek, R.; Schmittenbecher, P.; Schönau, E.; Wessel, L.; Wirth, T.; Mentzel, H.-J.; Creutzig, U. (Klinische Pädiatrie, 2014)
Musculoskeletal pain (MSP) is a common childhood complaint associated with multiple differential diagnoses, including cancer. Considering the expanding spectrum of diagnostics, evaluating a young patient with MSP is a challenge today, particularly for non-specialists in a primary care setting. Since childhood cancer is rare and most cardinal symptoms mimic rather non-serious diseases, misdiagnosis is not uncommon, but of significant prognostic relevance. To build the appropriate bridge between primary and secondary care for a child presenting with MSP, thereby preventing treatment delay and longterm sequelae, initial evaluation should follow a comprehensive, multidisciplinary, systematic and stepwise approach, which unites the patient’s individual anamnestic, psychosocial, and clinical characteristics. After a systematic review of the literature, we generated multidisciplinarily quality-assured recommendations for efficient, rational and cost-effective primary care assessment of pediatric MSP. The algorithm promotes the identification and structured interpretation of the patient’s individual clinical clues. It should serve the primary care physician to recognize when further intervention, rather than reassurance and follow-up, is needed using the minimum amount of testing to make an appropriate, prompt diagnosis in the clinical situation “child presenting with MSP”. A German version of this algorithm has been published in the Guideline-Portal of The Association of the Scientific Medical Societies (“Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften”, AWMF) in November 2013.
Keywords: children and adolescents; musculoskeletal pain; epidemiology; etiology; differential diagnosis; primary care